Dynamic disulfide/thiol homeostasis in lead exposure denoted by a novel method. (May 2017) - Bal, Ceylan; Ağış, Erol Rauf; Gündüzöz, Meşide; Büyükşekerci, Murat; Alışık, Murat; Şen, Orhan; Tutkun, Engin; Yılmaz, Ömer Hınç
Lead is a toxic heavy metal, and prevention of human exposure to lead has not been accomplished yet. The toxicity of lead is continually being investigated, and the molecular mechanisms of its toxicity are still being revealed. In this study, we used a novel method to examine thiol (SH)/disulfide homeostasis in workers who were occupationally exposed to lead. A total of 80 such workers and 70 control subjects were evaluated, and their native and total SH values were measured in serum using a novel method; their blood lead levels were also assessed. The novel method used for SH measurements was based on the principle of measuring native SH, after which disulfide bonds were reduced and total SHs were measured. These measurements allowed us to calculate disulfide amounts, disulfide/total SH percent ratios, disulfide/native SH percent ratios, and native SH /total SH percent ratios. We found that disulfide levels were significantly higher in workers who were exposed to lead (21.08(11.1–53.6) vs. 17.9(1.7–25), p < 0.001). Additionally, the disulfide/native SH and disulfide/total SH percent ratios were higher in exposed workers, while the native SH/total SH percent ratios were higher in the control subjects. Furthermore, the lead and disulfide levels showed a positive correlation, with p < 0.001 and a correlation coefficient of 0.378. Finally, the novel method used in this study successfully showed a switch from SH to disulfide after lead exposure, and the method is fully automated, easy, cheap, reliable, and reproducible. Use of this method in future cases may provide valuable insights into the management of lead exposure.